Perbedaan Coping Stress Penderita Kanker Ditinjau Dari Jenis Kelamin Di RSUP H. Adam Malik Medan - Ade Ari Isnainy; Laili Alfita (Faculty of Psychology, Universitas Medan Area, 2017)
Coping stress is an individual effort to reduce, tolerate, or overcome the stress caused by a source that is considered to burden the individual. This study aims to see differences in coping stress of cancer patients of men and women in RSUP H. Adam Malik Medan. Assuming that women's coping stress is higher than men, which means women are more able to clutch than men. The subjects of this study were patients with stage 3 and 4 cancer who underwent inpatient at RSUP H. Adam Malik Medan. This research is based on Guttman scale method which consists of 2 coping stress strategies that are problem focused coping and emotion focused coping. The data analysis technique used in this research used 1 lane variance analysis with F = 12,087 and coefisisen significant 0,002(p <0,05) . Based on the results of data analysis performed, then obtained the result that there are differences in coping stress male and female cancer, where, coping stress in men with cancer is in the low category, because the hypothetical mean 30 is greater than the empirical mean (28.7333) where the difference is less SD value (10,738). While coping stress in women with cancer is in the high category, because the hypothetical mean (30) is less than the empirical mean (57,333), where the difference exceeds the SD (8,208). This means that the phenomenon seen by the researchers in accordance with the data obtained during conducting research, which from this research is known that coping stress in women with cancer expressed high. This means the proposed hypothesis reads that there is a difference in coping stress in male and female cancer patients with the assumption that women are more able to clutch than men are accepted.